2018
DOI: 10.1177/0148558x17748524
|View full text |Cite
|
Sign up to set email alerts
|

Can Short Sellers Detect Internal Control Material Weaknesses? Evidence From Section 404 of the Sarbanes–Oxley Act

Abstract: We examine whether short sellers are interested in, and capable of, identifying firms with an upcoming revelation of internal control material weaknesses (ICMW). We show that short sellers accumulate positions in firms that are about to disclose ICMW under Section 404 of the Sarbanes–Oxley Act for the first time when internal control problems are severe. We find that the short-interest buildup is mainly due to the use of private rather than public information, which suggests that their trades contain increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Disclosure will not cause companies to overreact before the report is released [8], nor will it exacerbate price declines during short-selling declines on days of extreme negative returns [9], which indicated that impact of short-selling institution is rational even effective. However, it is not clear enough that the tendency of company's stock price and the possible changes of the whole market.…”
Section: Discussionmentioning
confidence: 99%
“…Disclosure will not cause companies to overreact before the report is released [8], nor will it exacerbate price declines during short-selling declines on days of extreme negative returns [9], which indicated that impact of short-selling institution is rational even effective. However, it is not clear enough that the tendency of company's stock price and the possible changes of the whole market.…”
Section: Discussionmentioning
confidence: 99%
“…First, although short-sellers can identify firms with significant internal control weaknesses, the evidence primarily focuses on material internal governance failures (Singer et al 2022). Considering the large sample size in this paper, the relationship should not be driven solely by these rare instances of material internal governance failure.…”
Section: Alternative Explanationmentioning
confidence: 95%
“…Related to the impact of short selling on corporate information transparency, The findings of Singer, Wang, and Zhang [13] also indicate that short selling traders could have private information of the internal control status of the companies because they found a sudden large short interest before the announcement of significant internal control deficiency by studying the short selling and internal control data from 2004 to 2010.…”
Section: The Specification Of the Governance Effect Of Short Selling mentioning
confidence: 99%